An Enhanced PID-Based Motion Control Framework for Autonomous Line-Following Robot - Nguyen-Thanh-Loc Tran; Viet-Tien-Dung Bui; Hong-Nho Bui; Hoang-Nguyen Nguyen; Thi-Ngoc-Thao Nguyen; Thanh-Sang Nguyen; Hung-Ky Nguyen; Huynh-Duc-Anh Nguyen; Thanh-Binh Phan; Hoang-Sang Luong; Le-Minh-Tan Nguyen; Vo-Minh-Khoa Tran; Tien-Dat Nguyen; Huynh-Khanh-Nam Pham; Duc-Dat Nguyen; The-Nhan Nguyen (Journal of Fuzzy Systems and Control, 2026)
PID controller is widely used in automatic control systems because it is simple, reliable, and easy to apply. It is especially suitable for mobile robots, such as line-following robots. The main contribution of this work is an experimental method to tune PID parameters. Instead of using complex algorithms, the parameters are adjusted and tested directly on a real robot. This makes the method easier to apply, especially for low-cost and educational systems. Experiments were conducted to evaluate how PID parameters (Kp, Ki, and Kd) affect the robot’s performance. The robot was tested on different paths, including straight lines, curves, and 90-degree turns. The results show that the optimal parameters are Kp = 65, Ki = 0.1, and Kd = 13. With these values, the robot moves smoothly, responds quickly, and follows the path accurately.